Modernity and Utopia - Škorić Gordana (2007)
Modernity as a paradigm of understanding culture has been diversly interpretes and a question arises whether is a single modernity, or a number of them. The text touches upon Weber, s interpretation of modernity, followed by the views of E. Grassi that took a different route to the understanding of the rational-irrational interrelation, and finally the tenets of postmodernity that in the various ways disturb the concept of modernity (vattimo and others authors) and offer insight into the important traits of modernity as such. In this context we are interested in the proper place of the utopian dimension (Bloch, Marcuse) and the question to what extent is it a part of the unfinished process of modernity (Habermas) and what significance it bears in the light of the relationship af art and culture.
Projekt MZOS
ENG